The Influence of Work-Life Balance, Workload, and Occupational Health and Safety on the Performance of Drivers at PT Tiga Putri Bersaudara IS 36 to Port - Anggraini, Bean Nur; Yuliani, Yuliani; Hadjri, Muhammad Ichsan (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the influence of work-life balance, workload, and occupational health and safety on the performance of drivers at PT Tiga Putri Bersaudara IS 36 to Port. The research adopts a quantitative approach with a causal design, where work-life balance, workload, and occupational health and safety are examined for their impact on the dependent variable, namely driver performance. The population in this study includes all drivers at PT Tiga Putri Bersaudara, totaling 140 individuals, with a saturated sampling technique employed. Data were collected through the distribution of questionnaires that measured the research variables using Likert scale indicators. For data analysis, the Structural Equation Modeling-Partial Least Square (SEM-PLS) method was used, with ordinal data converted to interval scale using the Method of Successive Interval (MSI). The results indicate a significant relationship between several work-related factors and driver performance at PT Tiga Putri Bersaudara IS 36 to Port. First, work-life balance has a positive and significant effect on driver performance, indicating that the better the balance between work and personal life, the higher the performance exhibited. Second, workload has a negative and significant impact on driver performance, suggesting that the heavier the workload perceived, the lower the resulting work performance. Third, occupational health and safety also have a positive and significant influence on driver performance, meaning that a safe work environment and well-maintained health conditions contribute to improved performance. These findings highlight the importance of addressing employee well-being and workload in efforts to enhance workforce productivity within the company.